(untitled) (Costos y Gestión, 2021)
The research work presented focuses on the proposal for calculating Activity-Based Cost at the El Yunque de Baracoa Base Business Unit located in the municipality of Baracoa, belonging to the Camping Company Popular Guantánamo, with the aim of proposing a procedure to calculate the Activity Based Cost , based on the study of the processes in the accommodation area of the UEB in question. The proposed procedure will facilitate the decision-making of UEB managers, since the current cost system lacks information to efficiently man-age the accommodation activity that the client demands. A wide search was made of criteria from different authors, on the evolution of Management Accounting, analyzing its main contributions and demonstrating the advantages of ABC over traditional costs. As a result of the research, it will improve the way of managing the resources and activities that are consumed and executed, allowing the company management to guide the implementation of this procedure to the rest of the UEB.